SUSTAINABILITY REPORTING AND FINANCIAL PERFORMANCE OF LISTED INDUSTRIAL GOODS SECTOR IN NIGERIA - Alhassan, Ismail; Islam, K. M. Anwarul; Haque, Md. Shariful (International Journal of Accounting & Finance Review, 2021)
The aim of this paper is to examine how sustainability reporting affects the performance of listed industrial goods companies in Nigeria. For a period of ten years, from 2011 to 2020. This study used time-series and cross-sectional analysis of selected listed industrial goods companies on the Nigerian Stock Exchange. Ex-Post Facto research was used in this study. Data were gathered from secondary sources such as fact books and financial statements of the companies in Nigeria. Using E-View 9.0 statistical software, the data were statistically analyzed using Pearson correlation coefficient and multiple regression analysis. The findings of this study demonstrated that, at a 5% level of significance, sustainability reporting (as measured by economic, environmental, and social performance indices) has a positive significant effect on return on assets, return on equity and earnings per share. The study proposes, among other things, that a standardized Sustainability Index be adopted, since this will assist to put pressure on firms to pay greater attention to their environment and take sustainable development issues more seriously.JEL Classification Codes: G32.